Postdepositional Mercury Mobility in a Permafrost Peatland from Central Yukon, Canada - Bandara, Sasiri; Froese, Duane G; St. Louis, Vincent L; Cooke, Colin A; Calmels, Fabrice (ACS earth and space chemistry, 2019)
Ombrotrophic peat underlain by permafrost has been used to reconstruct past atmospheric mercury (Hg) deposition. Here, we analyze a core collected from a rapidly aggrading, raised peat bog near Dawson City, Yukon, Canada, to reconstruct natural and anthropogenic Hg deposition rates during the last 400 years. Our results differ from previous accounts of atmospheric Hg deposition based on natural archives in the northern hemisphere. We observe a correlative link between total Hg concentrations and pore-water/ice δ18O signatures from the same depths in our core. In light of this relation, we recognize that a portion of atmospherically deposited Hg may be subject to downward mobility through the annually thawed active layer until it becomes perched at the impermeable top of permafrost. An irregular 210Pb activity profile provides further evidence for postdepositional metal mobility which is partly facilitated by chemo-physical interactions between complexing and solubilizing agents in organic-rich pore-waters of the active layer. This empirical evidence for postdepositional Hg and Pb mobility implies the need for caution when interpreting ombrotrophic peat from permafrost regions as high-resolution archives of atmospheric metal deposition.